Identitas nasional di tengah demam K-pop: Tantangan dan strategi generasi muda - Anatasia, Nadita Leli (Maliki Interdisciplinary Journal, 2025)
Globalization plays a role in the spread of K-Pop in Indonesia, especially among the younger generation. The K-Pop phenomenon was received with enthusiasm, which can be proven by the number of K-Pop fans in Indonesia. Through K-Pop, Korean culture is slowly entering so that it can shift local culture. There are negative and positive impacts caused by this K-Pop phenomenon. The K-Pop phenomenon is a challenge to maintain the value of national identity of the younger generation. To deal with it, an appropriate strategy is needed so that the consumption of foreign culture remains balanced with the preservation of local culture. This research uses qualitative research methods supported by accurate literature sources and questionnaire data that have been collected. The result of this research is to provide understanding to the younger generation to maintain their national identity despite being a K-Pop fan.